Determinants of National Health Insurance Membership among Indonesian Women with Live Births - Lely Khulafa'ur Rosidah; Rahma Novita Asdary; Siti Komariyah; Widya Kusumawati (JURNAL KEBIDANAN, 2023)
According to WHO statistics, the maternal mortality rate (MMR) in developed countries is estimated at 12/100,000 live births, while in Low and Middle-income countries (LMICs) is 239/100,000 live births. Whilst 99% of all maternal deaths were estimated to occur in LMICs, even though the causes of death can be prevented with the right policies considering that one of the goals of the Sustainable Development Goals is to reduce MMR. Access to the maternal health care (MHC) is the main technique to reduce maternal morbidity and mortality. The study evaluated the factors that influence Indonesia’s national health insurance ownership, Jaminan Kesehatan Nasional (JKN), among women who utilize MHC in Indonesia. Methods: We used data from the 2017 Indonesia Demographic and Health Survey (IDHS) on women with live births (n=5429) in 2016-2017. We conducted analyses at the national level using descriptive statistics and logistic regression through RStudio software Results: Out of 5717 samples, 61.4% were insured by JKN and 38.6% were uninsured. Women in white-collar employment were 2.37 times (95%s CI = 1.77-2.59) more likely to be insured by JKN, and those living in urban areas had a 1.39 (95% CI = 1.18-1.44) higher chance of being enrolled in JKN. Conclusion: The study concluded that employment status and place of residence were significant determinants of health insurance ownership in Indonesia.